Effects of pre-transplant L-carnitine supplementation on primary graft dysfunction in liver transplant recipients: a pilot, randomized, placebo-controlled clinical trial - Behrouz Khajeh; Simin Dashti-Khavidaki; Mohsen Nasiri-Toosi; Keyhan Mohammadi; Atefeh Jafari (Wolters Kluwer Medknow Publications, 2019)
Primary graft dysfunction (PGD) and non-function (PNF) happen in 8.7-24.7% and 0.9-7.2% of liver transplant recipients, respectively. These phenomena increase treatment cost and patients' death. This study assessed the effect of L-carnitine supplementation on the incidences of PNF/PGD in liver transplant recipients. This randomized, placebo-controlled, clinical trial was performed on adult liver transplant recipients. Patients took L-carnitine syrup 500 mg three times daily or placebo from the time of including in transplant waiting list until the day of transplant surgery (median 14 days, 1-192 days). Thirty-three patients in L-carnitine and 39 patients in placebo group completed the study. Although not statistically significant, PNF and PGD happened less frequently among recipients in L-carnitine compared with placebo group (3% vs. 12.8% for PNF; 15.2% vs. 30.8% for PGD). Alanine aminotransferase (ALT) and aspartate aminotransferase were lower in L-carnitine group at day 3 after transplantation. ALT declined more significantly within 48 h after transplantation in L-carnitine arm (median 120.50 vs. 79 IU/L; P = 0.03). One-month patients' survival was significantly higher in L-carnitine versus placebo group (97% vs. 74.4%; P = 0.008). The rates of PNF and PGD in L-carnitine group were approximately one-fourth and one-half of placebo group respectively. One-month patients' survival was higher in L-carnitine group.